The Effect of Liquidity, Leverage, and Operating Capacity on Financial Distress with Managerial Ownership as a Moderating Variable - Larasati, Hanum; Wahyudin, Agus (Universitas Negeri Semarang, 2019)
This study intends to examine the effect of liquidity, leverage, and operating capacity ratio on financial distress risk with managerial ownership as moderator. The population of this study was all of the property, real estate and construction services companies listed on the IDX in 2013-2017 as many as 55 companies. This study used purposive sampling technique for the selection of samples that produced 17 companies or 68 analysis units. Moderation regression was used as analytical method in this study with SPSS 23 as the analytical tool. This research shows that liquidity does not affect on financial distress risk, while leverage and operating capacity affect on financial distress risk. Managerial ownership is able to moderate the effect of leverage ratio and operating capacity on financial distress risk, but is not able to moderate the effect of liquidity on financial distress risk. The conclusion of this study is that the financial distress risk is influenced by leverage, operating capacity, leverage moderated by managerial ownership, and operating capacity moderated by managerial ownership.